(untitled) (Journal of Social Sciences Review, 2023)
The study analyzed the perceptions of high-achieving students regarding the reasons behind their academic success. Conducted in Punjab, Pakistan, the research involved students from three different education boards in cities like Gujranwala, Faisalabad, and Lahore. The sample consisted of 36 students, equally divided between genders, randomly selected from each board. These students attributed their achievements to factors like determination, hard work, and proficiency. The primary reasons for their success were identified as dedication, effort, and ability. Notably, high achievers tended to avoid tasks related to success, as they believed their accomplishments were a result of their inherent skills and hard work, and failures were attributed to bad luck. Despite some limitations, the study revealed that successful individuals emphasized the influence of internal factors after achieving success. The research highlighted the importance of capable individuals not only controlling outcomes but also taking responsibility for their accomplishments. The study aimed to explore the factors, both internal and external, that high achievers attribute to their success.